THE EXISTENCE AND UNIQUENESS OF THE MILD SOLUTION TO A NONLINEAR CAUCHY PROBLEM ASSOCIATED WITH A NONLOCAL REACTION-DIFFUSION SYSTEM - Guswanto, Bambang Hendriya; Bin Admon, Mohd. Ariff; Binti Lim Boon Chye, Nur Natasha (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2019)
ABSTRACT. We study the existence and uniqueness of a mild solution to a nonlinear Cauchy problem associated with a nonlocal reaction diffusion system by employing the properties of analytic semigroup operator generated by the linear part of the problem which is sectorial and then applying Banach Fixed Point Theorem to the problem. We show that the problem has a unique mild solution under a Lipschitz condition on the nonlinear part of the problem. An example as an application of the result obtained is also given.Keywords: existence, uniqueness, mild solution, nonlinear Cauchy problem, Banach fixed point theorem. ABSTRAK. Kita mengkaji keujudan dan ketunggalan penyelesaian lemah masalah Cauchy nonlinier yang berkaitan dengan sistem reaksi difusi nonlokal dengan menggunakan sifat-sifat operator semigrup yang dibangkitkan oleh operator pada bagian liniernya yang bersifat sektorial dan kemudian menerapkan Teorema Titik Tetap Banach pada masalah tersebut. Kita tunjukkan bahwa masalah tersebut memiliki penyelesaian lemah yang unik atas kondisi Lipschitz untuk operator pada bagian nonliniernya. Satu contoh sebagai penerapan hasil yang diperoleh juga diberikan.Kata kunci: keujudan, ketunggalan, penyelesaian lemah, masalah Cauchy nonlinier, teorema titik tetap Banach.